Crime of Padre Amaro - Carrera, Carlos (2002)
International superstar Gael Garcia Bernal ( Y Tu Mama Tambien, Amores Perros) stars in the most "Riveting, incendiary and provocative" (Megan Turner, NEW YORK POST) movie of the year. A recently ordained priest (Bernal) is sent to help an aging priest run a small parish church in rural Mexico. Upon arriving at his new post, he meets a beautiful young woman with a religious passion that borders on obsession. Quickly, her passion for her faith becomes helplessly entangled in a growing attraction to the new priest. But when the handsome priest crosses the line that separates temptation from sin, he finds himself torn between the divine and the carnal, the righteous and the unjust.